Perencanaan Beton Struktural Pelat Berdasarkan SNI 1726-2019 Untuk Bangunan Apartemen Di Palembang - Ramadhan, Alwi Neva (Universitas Negeri Surabaya, 2023)
Based on the background statement above, a formulation of the problem can be drawn: 1. How to calculate the slab structure. Research objectives 1. To find out the floor slab structure planning Research flow chart in Figure 3.1. This research method uses two ways of data collection techniques, namely primary data and secondary data. The sequence of stages used for research is as follows: 1) Literature Study Data Collection: Shop Drawing or Forcon, Examples of conversion calculations for slab/floor plate structures, and regulations or SNI related to the calculation of slab/floor slab structure planning ? Planning Data 1 L1 5 m L2 5 m L3 5 m L4 5 m 2. Column Height H1 3.75 m H2 4.75 m H3 4.75 m 3. Portal Distance 4 m 4. Building Length 44 m 5. Quality material: Fy 400/240 Mpa Fc 25 Mpa The conclusion of this calculation article is an Apartment in Palembang City which has a size of 20 m x 44m, Based on calculations that have been carried out in accordance with SNI 1726-2019, using a thick slab or floor plate with a thickness of 120mm with a floor plate style 2 way. Using size D10-200 x direction reinforcement, D10-150 y direction reinforcement, D10-400 shrinkage reinforcement.